Learning Module Innovation Interactive for Counseling Guidance: Technology Integration in Increase Intelligence Emotional Student - Yusnitarini, Fera; Firdaus, Rangga (Jurnal Evaluasi dan Pembelajaran, 2025)
Emotional intelligence is an important component in learner development, especially in facing social and psychological challenges during adolescence. Counselling has a strategic role in helping students recognize, understand and manage emotions in a healthy way. However, traditional approaches to counselling services in schools often lack interactivity, making it difficult to actively engage students. With the development of technology, there is an opportunity to integrate technology-based learning modules in counselling guidance services to create a more interesting and applicable learning experience. This study aims to develop a technology-based interactive learning module using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model that focuses on improving students' emotional intelligence. The module is designed to strengthen students' emotional competencies, such as self-awareness, stress management, empathy, and social skills. The results showed that after the implementation of this technology-based module, there was a significant improvement in students' emotional intelligence, with an average score of 18% improvement in self-awareness competency, 22% in stress management, 19% in empathy, and 21% in social skills. In addition, 85% of students reported a more interactive and relevant learning experience, and 90% of teachers reported increased effectiveness in the implementation of counselling guidance. These findings make an important contribution to the development of learning media innovations for counselling guidance in the digital era.